PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP KETERAMPILAN MEMBUAT KALIMAT SISWA KELAS II SDN 12 GU KABUPATEN BUTON TENGAH PROVINSI SULAWESI TENGGARA - Dwi Astuti Arifin; Aco Karumpa; Akbar Avicenna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Picture and Picture learning model on the sentence-making skills of second grade students at SDN 12 Gu, Central Buton Regency, Southeast Sulawesi Province. This research was motivated by the low ability of students in constructing sentences in Indonesian language learning and the lack of variation in learning models used by teachers. This study used a quantitative approach with an experimental research type employing a One Group Pretest-Posttest Design. The sample of this study consisted of 20 students from class II C. Data collection techniques were conducted through pretest and posttest instruments. The data were analyzed using descriptive and inferential statistics through the t-test with the help of SPSS application. The results showed that the average pretest score of students was 58.2 and increased significantly after the implementation of the Picture and Picture learning model. The results of the Independent Samples t-Test showed a significance value of < 0.001 < 0.05, indicating that H₀ was rejected and H₁ was accepted. Thus, there was a significant effect of the use of the Picture and Picture learning model on students’ sentence-making skills. The Picture and Picture learning model proved to be effective in improving students’ activeness, creativity, and ability to arrange sentences logically and systematically. Therefore, this learning model can be used as an alternative learning strategy in Indonesian language learning, especially in improving sentence-making skills for elementary school students.